Ensino coletivo de bateria e percussão: proposição e análise de um método com ênfase na criatividade - Holanda, Marcelo Anderson da Costa (2023)
The objective of this Master's dissertation was to propose and analyze a collective teaching method for drums and percussion, called “Creative Repercussion”. This method has an emphasis on creation, and it was applied in the disciplines of Art, which appear in the curricular matrix of Integrated Technical Education courses, such as IT, Mechanics and Buildings at the Federal Institute of Education, Science and Technology of Ceará (IFCE) Campus Itapipoca, from August to December 2022. The results were collected and analyzed in March 2023. For the development of this dissertation, were used as theoretical references authors from the area of Collective Teaching of Musical Instruments (ECIM) such as Cruvinel (2005), Santos (2013) and others, and from the area of creativity such as Swanwick (2003), Schafer (2011), Beineke (2009), among other authors. The methodology consisted of developing and applying a collective teaching method for drums and percussion. The approach to the research problems was qualitative, following the studies of Bodgan and Biklen (1994) and Minayo (2012). The evaluation of the participants perception of the collective drum and percussion method was carried out by applying a form filling to the research participants and was based on the discussion of data, considering creativity in the context of music teaching, as also results from ECIM, from musical theory applied together with instrumental practice, access to music within the school environment, factors of motivation and/or demotivation of instrumental practice, the use of a regional repertoire and the use of technologies, such as metronome. Thus, this work brings contributions to ECIM in the area of Drums and Percussion within the scope of Basic Education, as well as with the use of creativity in the school context in Art subjects in the music subarea.